KUALITAS ORGANOLEPTIK BAGIAK DENGAN FORTIFIKASI TEPUNG KACANG GUDE (Cajanus cajan) - Setyawan, Bagus; Rosiana Ulfa; Arfiati Ulfa Utami (Program Studi Teknologi Hasil Pertanian Universitas PGRI Banyuwangi, 2024)
Bagiak is a typical snack from Banyuwangi and is one of the archipelago's culinary heritages that is still a favorite. However, to improve the nutritional content and quality of Bagiak, there is a need for new innovations in making Bagiak. One alternative solution is to make Bagiak through fortification of mung bean flour. The challenge is that the utilization of pigeonpea to be processed into food is still rare, so it is still less common in the community. Therefore, this study aims to analyze the organoleptic quality of fortified pigeonpea flour. This research is a type of experimental research conducted in July-September 2024. The experimental design uses one factor, namely the addition of mung bean flour at P0 (0%), P1 (15%), P2 (30%), P3 (45%), P4 (60%), P5 (75%). The panelists used were 75 people who were untrained panelists. The organoleptic parameters studied were the quality of taste, aroma, texture, and color. Data analysis used a Likert scale to determine the acceptability of panelists for the pigeonpea. Based on the results of organoleptic testing that has been carried out on 75 panelists, it can be seen that the P2 treatment (addition of 30% pigeon pea flour) is the most favored by panelists. This can be seen from the score of the flavor parameter of 91%, aroma of 92%, color of 91%, and texture of 88%. The conclusion of this study is that Bagiak with fortification of mung bean flour is very well received by panelists, especially in the P2 treatment (30%) where the final average acceptance score of panelists is 91% which means very good. Therefore, there is a need for more utilization of mung beans as an additional ingredient in various foods.